Co‐building a training programme to facilitate patient, family and community partnership on research grants: A patient‐oriented research project - Ingrid Nielssen; Sadia Ahmed; Sandra Zelinsky; Brian Dompe; Paul Fairie; Maria J. Santana (Health Expectations, 2023)
Abstract Introduction Patient engagement in patient‐oriented research (POR) is described as patients collaborating as active and equal research team members (patient research partners [PRPs]) on the health research projects and activities that matter to them. The Canadian Institutes of Health Research (CIHR), Canada's federal funding agency for health research, asks that patients be included as partners early, often and at as many stages of the health research process as possible. The objective of this POR project was to co‐build an interactive, hands‐on training programme that could support PRPs in understanding the processes, logistics and roles of CIHR grant funding applications. We also conducted a patient engagement evaluation, capturing the experiences of the PRPs in co‐building the training programme. Methods This multiphased POR study included a Working Group of seven PRPs with diverse health and health research experiences and two staff members from the Patient Engagement Team. Seven Working Group sessions were held over the 3‐month period from June to August 2021. The Working Group worked synchronously (meeting weekly online via Zoom) as well as asynchronously. A patient engagement evaluation was conducted after the conclusion of the Working Group sessions using a validated survey and semi‐structured interviews. Survey data were analysed descriptively and interview data were analysed thematically. Results The Working Group co‐built and co‐delivered the training programme about the CIHR grant application process for PRPs and researchers in five webinars and workshops. For the evaluation of patient engagement within the Working Group, five out of seven PRPs completed the survey and four participated in interviews. From the survey, most PRPs agreed/strongly agreed to having communication and supports to engage in the Working Group. The main themes identified from the interviews were working together‐communication and supports; motivations for joining and staying; challenges to contributing; and impact of the Working Group. Conclusion This training programme supports and builds capacity for PRPs to understand the grant application process and offers ways by which they can highlight the unique experience and contribution they can bring to each project. Our co‐build process presents an example and highlights the need for inclusive approaches, flexibility and individual thinking and application. Patient or Public Contribution The objective of this project was to identify the aspects of the CIHR grant funding application that were elemental to having PRPs join grant funding applications and subsequently funded projects, in more active and meaningful roles, and then to co‐build a training programme that could support PRPs to do so. We used the CIHR SPOR Patient Engagement Framework, and included time and trust, in our patient engagement approaches to building a mutually respectful and reciprocal co‐learning space. Our Working Group included seven PRPs who contributed to the development of a training programme. We suggest that our patient engagement and partnership approaches, or elements of, could serve as a useful resource for co‐building more PRP‐centred learning programmes and tools going forward.